Efektivitas Model Pembelajaran Inkuiri Terbimbing Berbantu Lembar Kerja Siswa Berbasis Saintifik Terhadap Hasil Belajar Siswa - Roswita Lioba Nahak; Vera Rosalina Bulu (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The objective of the research is to find out the effectiveness of the application of guided inquiry learning models to student learning outcomes. The research method used quasi-experimental with a nonequivalent control group design type. The population covered 34 students with saturated sampling technique with a sample of 34 students. The research instrument used test questions and documentation studies as well as data analysis techniques using the independent t-test and effect size test. The results of the study showed that the application of guided inquiry-based learning models with scientific-based worksheets on the learning outcomes of Class VI natural science at SDI Bakunase Kupang was effective, in which the average test score of the control class was smaller than the experimental class at 68.24 <79.41 and based on the value of sig. (2-tailed)> α that is 0.001 <0.05, then there was a significant difference in the average value between the control class and the experimental class and the effect size test results was 0.85. Therefore, it can be concluded that the application of the guided inquiry learning model based on LKS based Scientific is effective towards the learning outcomes of Class VI Natural Sciences at SDI Bakunase Kupang.